The complete mitochondrial genome of the orange-spotted grouper Epinephelus coioides (Perciformes, Serranidae). (3rd May 2016) - Yang, Huirong; Xie, Zhenzhen; Li, Shuisheng; Wu, Xichao; Peng, Cheng; Zhang, Yong; Lin, Haoran
Abstract: We present the complete mitochondrial genome of Epinephelus coioides in this study. The mitochondrial genome is 16, 458 bp in length, containing 13 protein-coding genes, 2 rRNA genes, 22 tRNA genes and a control region. All of them are encoded on the heavy strand except ND6 and 8 tRNA genes on the light strand. The nucleotide compositions of the light strand are 28.88% of G, 28.75% of T, 26.58% of A and 15.80% of C. All the protein-coding genes share ATG initiation codon except ATP6 with CTG and COXI with GTG, and four types of inferred termination codons are T (ND2, COXII, ND3, ND4 and Cytb), TA (COXIII), TAA (ND1, ATP8, ND4L, ND5, ATP6 and COXI) and TAG (ND6). There are 10 intergenic spacers, 5 gene overlaps and no tandem repeat sequence. Gene arrangement and distribution are consistent with the typical vertebrates.